Four-month incidence of suicidal thoughts and behaviors among healthcare workers after the first wave of the Spain COVID-19 pandemic. (May 2022) - Mortier, P.; Vilagut, G.; Alayo, I.; Ferrer, M.; Amigo, F.; Aragonès, E.; Aragón-Peña, A.; Asúnsolo del Barco, A.; Campos, M.; Espuga, M.; González-Pinto, A.; Haro, J.M.; et al.
Abstract: Healthcare workers (HCW) are at high risk for suicide, yet little is known about the onset of suicidal thoughts and behaviors (STB) in this important segment of the population in conjunction with the COVID-19 pandemic. We conducted a multicenter, prospective cohort study of Spanish HCW active during the COVID-9 pandemic. A total of n = 4809 HCW participated at baseline (May–September 2020; i.e., just after the first wave of the pandemic) and at a four-month follow-up assessment (October–December 2020) using web-based surveys. Logistic regression assessed the individual- and population-level associations of separate proximal (pandemic) risk factors with four-month STB incidence (i.e., 30-day STB among HCW negative for 30-day STB at baseline), each time adjusting for distal (pre-pandemic) factors. STB incidence was estimated at 4.2% (SE = 0.5; n = 1 suicide attempt). Adjusted for distal factors, proximal risk factors most strongly associated with STB incidence were various sources of interpersonal stress (scaled 0–4; odds ratio [OR] range = 1.23–1.57) followed by personal health-related stress and stress related to the health of loved ones (scaled 0–4; OR range 1.30–1.32), and the perceived lack of healthcare center preparedness (scaled 0–4; OR = 1.34). Population-attributable risk proportions for these proximal risk factors were in the range 45.3–57.6%. Other significant risk factors were financial stressors (OR range 1.26–1.81), isolation/quarantine due to COVID-19 (OR = 1.53) and having changed to a specific COVID-19 related work location (OR = 1.72). Among other interventions, our findings call for healthcare systems to implement adequate conflict communication and resolution strategies and to improve family-work balance embedded in organizational justice strategies.